Search for sustainable pension system and state support for funded pensions in CEE countries - Poškutė, Virginija; Gudaitis, Tadas; Medaiskis, Teodoras; Mečkovski, Jaroslav (Business: Theory and Practice, 2022)
Pension systems around Europe are being reformed for several decades already. Main objectives of the reforms are to enable people to have adequate income at retirement and to ensure the system’s financial sustainability. Many European countries implemented policies aiming at diversification of financing sources of income at older age: risk-sharing between pay-as-you-go and funded pensions is expected to help in achieving social policy objectives towards pension systems. Central and Eastern European countries (CEE) face even more challenges in ensuring adequate income at retirement. First, CEE countries were required to transform radically their economies in 1990s towards market economy, including old age pension systems. Second, in order to ensure diversified future old age pension income and attract more financial means to the system, introduction of funded pensions from scratch and ensuring as wide as possible coverage with funded pension schemes was of primary importance also. The paper discusses latest developments of retirement pension systems in Europe and state involvement in private pension schemes. In doing so, the focus is on the introduction of funded private pension schemes in selected CEE countries. In spite of initially chosen different paths for the reforms, inconsistent state policies towards funded pensions in the CEE countries resulted in similar outcomes of the reforms. The paper starts with discussion on main objectives of pension systems – enabling people to have adequate income at retirement and ensuring financial sustainability of the systems. Further, possibilities to achieve the objectives of pension reforms are analysed – diversification of income at retirement. Third part of the paper discusses prevailing debates on future of welfare state as such and individualisation trends within different European welfare state models. These debates and perceptions of population about responsibilities of a state for individual welfare affect direction of reforms and future shape of old age pension systems. Fourth part of the paper deals with state policies and tools that are used for encouragement of participation in supplementary pensions. Final part of the paper presents more detailed outline of the pension reforms in selected CEE countries and summarises particular challenges of their pension systems. The paper ends with a discussion on policy implications in relation to latest developments of pension systems in CEE countries.